Respostas

2014-04-15T10:04:35-03:00
Encontre a raiz da equaçao: X2-x=0

X2 - x=0
x² - x = 0

tem varias maneiras de FAZER

X² - x = 0   por em evidência

x(x - 1) = 0
x = 0      e  
(x - 1) = 0
x - 1 = 0
x = 1

outra maneira é a baskara

X² - X = 0      ----------- a = 1         b= - 1       c= 0
Δ= b² - 4ac
Δ= (-1)² - 4(1)(0)
Δ= 1 - 0
Δ= 1     se  Δ>0    então x = -b +-√Δ/2a

x' = -(-1) - √1/2(1)
x' = 1 - 1/2
x' = 0/2      _______________x' = 0 

x" = -(-1) + 1/2
x" = 1 + 1 /2
x" = 2/2
x" = 1___________________x" = 1
     
 




 
1 1 1